Unser Märchenschatz - 10 Film-Klassiker - Schmenger, Ursula; Bals, Karl-Heinz; Bleiweiß, Celino; Fürneisen, Bodo; Hübner, Wolfgang; Hattop, Karola (Studio Hamburg, 2021)
10 Märchenklassiker nach den Brüdern Grimm, Hans Fallada, Theodor Storm u.a für die ganze Familie. [www.der-ostfilm.de]
Keywords: DVD-Video